2017
DOI: 10.1016/j.brainres.2017.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Dietary restriction reduces hippocampal neurogenesis and granule cell neuron density without affecting the density of mossy fibers

Abstract: The hippocampal formation undergoes significant morphological and functional changes after prolonged caloric and dietary restriction (DR). In this study we tested whether prolonged DR results in deleterious alterations in hippocampal neurogenesis, density of granule cell neurons and mossy fibers, all of which support plasticity in the dentate gyrus. Young adult animals either experienced free access to food (control condition), or every-other-day feeding regimen (DR condition) for 3 months. The number of Ki-67… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…For morphometric analysis of the density of mossy fiber projections, dorsal hippocampal sections (representing −2.56 and −4.8mm from bregma, 4 sections per rat) were separately stained for synaptoporin (1:50, Rabbit polyclonal, SynapticSystems) followed by biotin-tagged secondary antibodies and visualized with DAB (Staples et al , 2017). For mossy fiber density, images were captured at 10x and synaptoporin in the hilus of the dorsal DG was evaluated by quantifying DAB stain (% area stained; (Galinato et al , 2018)) using ImageJ software (NIH).…”
Section: Methodsmentioning
confidence: 99%
“…For morphometric analysis of the density of mossy fiber projections, dorsal hippocampal sections (representing −2.56 and −4.8mm from bregma, 4 sections per rat) were separately stained for synaptoporin (1:50, Rabbit polyclonal, SynapticSystems) followed by biotin-tagged secondary antibodies and visualized with DAB (Staples et al , 2017). For mossy fiber density, images were captured at 10x and synaptoporin in the hilus of the dorsal DG was evaluated by quantifying DAB stain (% area stained; (Galinato et al , 2018)) using ImageJ software (NIH).…”
Section: Methodsmentioning
confidence: 99%
“…Water maze experiments were performed at relatively cold water (21°C), which heavily affects water maze performance ( Salehi et al, 2010 ). Staples et al (2017) , however, found reduced dentate gyrus neurogenesis and granule cell density in forced food restricted rats, when restriction started at an age of 2 months, whereas Lee et al (2000) found increased neurogenesis after dietary restriction started at an age of 3 months and lasting for 3 months in rats.…”
Section: Discussionmentioning
confidence: 92%
“…For morphometric analysis of the density of mossy fiber projections, dorsal hippocampal sections (representing −2.56 and −4.8 mm from bregma, 4 sections per rat) were separately stained for synaptoporin [29]. For mossy fiber density, images were captured at 10× and the mossy fiber tracts were combined for density measures.…”
Section: Methodsmentioning
confidence: 99%